The Effectiveness of Psychoeducational Groups with Homeroom Techniques to Improve Understanding of Premarital Sex among Students - Muslikah; Himma, Amirah Dzatul (Bisma The Journal of Counseling, 2022)
The purpose of this study was to determine the effectiveness of psychoeducational groups with homeroom techniques in increasing understanding about the dangers of premarital sex. The type of research used is experimental research with a one-group pretest-posttest design. The sample used was 7 grade XI students of SMAN 11 South Tangerang City who had a low understanding of the dangers of premarital sex. The sampling technique in this research is purposive sampling. The data collection method used is descriptive percentage analysis and Wilcoxon test. The results of this study indicate that students' understanding of the dangers of premarital sex before and after being given treatment in the form of a homeroom technique psychoeducation group increased by an average of 6.62%. The effectiveness of the psychoeducational group with the homeroom technique is marked by a change in understanding of the dangers of premarital sex. This can be seen from the comparison between the results of the pretest which are categorized as moderate to close to low and the posttest results which increase after being given treatment into the high category. Suggestions for further researchers, it is necessary to conduct similar research by studying the weaknesses in this research, or by developing this research by replacing techniques with more innovative and relevant to the conditions of the research subjects.